Framings Influence on the Governance of Climate Change Adaptation and Risk Management at the Local Level: The cases of Upala in Costa Rica and San Francisco del Valle de Ocotepeque Honduras - Segura-Ramírez, Luis Diego (2023)
Climate change is one of the main global challenges of the 21st century. The international agenda has come a long way since the approval of the United Nations Framework Convention on Climate Change. The international community has understood that the mitigation agenda will not be enough to address the problems associated with climate change and the latest international instruments have incorporated adaptation as a central issue in the response to it. States have been approving Nationally Determined Contributions within the framework of the Paris Agreement. In these contributions, the generation of public policy to promote adaptation at the national level has been established as a central element. However, a fundamental challenge of adaptation is that it must be studied and developed locally; therefore, national, and international instruments can stimulate and promote these processes. Nevertheless, it will be the local authorities and actors who will determine the progress of these processes. This article focuses on analyzing the influence of actors and their frames of reference in local planning processes and the integration of adaptation to climate change. We studied the cases of Upala, Alajuela in Costa Rica, and San Francisco del Valle de Ocotepeque in Honduras, with the aim of understanding how these frameworks influenced the development of local public policies that integrated risk management and climate change adaptation measures. The results show that the referential frameworks of the actors influence the way in which risk and climate change are understood and the assessment of the measures that were included in the local plan.Thus, using comparative case studies applied to countries is a key tool for analyzing international phenomena. Although adaptation is a locally led process, its study, practice, and instruments that facilitate its progress demand research processes that allow the different practices and associated problems to be compared internationally. From the international relations agenda, the study of these adaptation practices of different countries is a key tool in the analysis of the international agendas for adaptation and response to climate change.